1997
DOI: 10.1097/00004647-199704000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Concentration after Cardiopulmonary Resuscitation Influences Functional Neurological Recovery in Human Cardiac Arrest Survivors

Abstract: Experimental data suggest that postischemic blood glucose concentration plays an important role in modulating both ischemic cerebral infarction and selective neuronal necrosis. This study investigated the association between functional neurological recovery and blood glucose concentrations in human cardiac arrest survivors. A group of 145 nondiabetic patients were evaluated after witnessed ventricular fibrillation cardiac arrest. Data regarding cardiac arrest were collected according to an internationally acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(60 citation statements)
references
References 46 publications
1
50
1
8
Order By: Relevance
“…10,[65][66][67][68][69][70] Animal studies suggest that elevated postischemic blood glucose concentrations exacerbate ischemic brain injury, 71,72 and this effect can be mitigated by intravenous insulin therapy. 73,74 Seizures in the post-cardiac arrest period are associated with worse prognosis and are likely to be caused by, as well as exacerbate, post-cardiac arrest brain injury.…”
Section: Post-cardiac Arrest Brain Injurymentioning
confidence: 99%
“…10,[65][66][67][68][69][70] Animal studies suggest that elevated postischemic blood glucose concentrations exacerbate ischemic brain injury, 71,72 and this effect can be mitigated by intravenous insulin therapy. 73,74 Seizures in the post-cardiac arrest period are associated with worse prognosis and are likely to be caused by, as well as exacerbate, post-cardiac arrest brain injury.…”
Section: Post-cardiac Arrest Brain Injurymentioning
confidence: 99%
“…No difference in arrhythmias was noted in the two groups. Cooling also leads to hyperglycaemia (8,13), which in itself has been linked to bad outcome (23,38,39). Most authors now agree that insulin infusion to secure normoglycaemia should be a standard part of neurointensive care (8,13,15,26,27,29,32).…”
Section: Complications and Safety Issuesmentioning
confidence: 99%
“…Non-intervention studies have shown increased mortality among cardiac arrest patients with high levels of blood glucose 60,67,68 (GOE IV-V). Aggressive insulin treatment in patients with critical illness has reduced long-time mortality 69 (GOE I). Thus, hyperglycaemia should be avoided and treated with insulin infusions (GOR B).…”
Section: Timing Of Other Interventionsmentioning
confidence: 99%